Formation of Tax System of Ukraine - Орлова, В. К.; Кафка, С. М. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
Ukraine celebrated the twenty-four years of its independence. Throughout this period, the country's tax reform takes place. The article describes in chronological order all the stages of this reform, marked the early years, analyzed the changes in taxation that occurred in 1997, 2011, 2014, and the characteristic of the models proposed tax reforms that are being discussed.